2018
DOI: 10.1371/journal.pntd.0006630
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of a 0.005% fipronil bait, orally administered to Rhombomys opimus, for control of fleas (Siphonaptera: Pulicidae) and phlebotomine sand flies (Diptera: Psychodidae) in the Central Asian Republic of Kazakhstan

Abstract: Plague (Yersinia pestis) and zoonotic cutaneous leishmaniasis (Leishmania major) are two rodent-associated diseases which are vectored by fleas and phlebotomine sand flies, respectively. In Central Asia, the great gerbil (Rhombomys opimus) serves as the primary reservoir for both diseases in most natural foci. The systemic insecticide fipronil has been previously shown to be highly effective in controlling fleas and sand flies. However, the impact of a fipronil-based rodent bait, on flea and sand fly abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 74 publications
(94 reference statements)
1
22
1
Order By: Relevance
“…Oral treatments (e.g. treated baits [ 27 ] or chewable tablets [ 28 , 29 ]) could be used to significantly reduce dog handling.…”
Section: Introductionmentioning
confidence: 99%
“…Oral treatments (e.g. treated baits [ 27 ] or chewable tablets [ 28 , 29 ]) could be used to significantly reduce dog handling.…”
Section: Introductionmentioning
confidence: 99%
“…Since simulation results suggest that larval mortality has greater impact on P. argentipes populations than adult mortality, fipronil application would be more efficacious in areas with greater FOF. Several studies have indicated phlebotomine sand fly sensitivity to fipronil [26,[29][30][31][32], with P. argentipes larvae being particularly vulnerable [32]. Poché et al recorded 100% larval mortality up to 21-days post treatment at all fipronil concentrations they administered to cattle (Bos taurus) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cattle are often heavily infested with ectoparasites such as ticks in India, which in addition to leading to disease transmission causes extensive harm to livestock production and health [70]. Prior research indicates that oral fipronil can remove ticks [23] and fleas [24,26] infesting rodents under laboratory and field conditions. Poché et al [32] noted a significant decrease in tick numbers on cattle treated orally with a single dose of 0.5 mg/kg fipronil under pen conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventive treatments with other insecticides including fipronil and cypermethrin were not associated with reduced feeding, and neither product used alone is indicated against sandflies and leishmaniasis control in dogs. However, in a recent field study, fipronil baits given to Rhombomys opimus rodents, reservoirs of L. major in central Asia, significantly reduced gravid female abundance (Poché et al ., ), and cypermethrin was found to be effective in controlling L. longipalpis sandflies when sprayed on the walls of human residences in Brazil (Barata et al ., ). It should be stressed, however, that none of the commercially available insecticide treatments against sandflies have repellent activity that is 100% effective, and studies in dogs suggest that sandfly biting frequencies and feeding preferences may vary among individuals of the same species (Risueño et al ., 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%